Alcalar and the Management of the Resources of Its Territorial Environment in the 3rd Millennium BCE - Morán, Elena (2018)
The results of the excavations, geophysical surveys, bioanthropological studies, studies of faunas and plants and radiocarbon dates of the various contexts, allowed to propose a model for the organisation of the Alcalar settlement, situated in the extreme south of Portugal, which from 2800 BCE was established as a large population agglomerate, with the functions of a power centre. The geographical diversity of the Alcalar territory, the maritime routes and land crossings provided access to a wide variety of resources to its inhabitants. The presence of exogenous materials and artefacts, although poorly represented, confirms the existence of exchange networks, mainly with Alentejo and Andalusia, but without discarding routes to Atlantic Europe and the Mediterranean.